Initial Evaluation of the Pediatric PROMIS® Health Domains in Children and Adolescents With Sickle Cell Disease. Issue 6 (19th February 2016) - Dampier, Carlton; Barry, Vaughn; Gross, Heather E.; Lui, Yang; Thornburg, Courtney D.; DeWalt, Darren A.; Reeve, Bryce B.
Abstract : Background: The Patient Reported Outcomes Measurement Information System (PROMIS®) has developed pediatric self‐report scales measuring several unidimensional health attributes (domains) suitable for use in clinical research, but these measures have not yet been validated in sickle cell disease (SCD). Procedure: A convenience sample of SCD children, aged 8–17 years, from two sickle cell programs was recruited at routine clinic visits, including some for hydroxyurea monitoring or monthly transfusions. Children completed PROMIS pediatric items using an online data collection platform, the PROMIS Assessment Center Web site. Results: A total of 235 participants (mean age 12.5 ± 2.8 years, 49.8% female) participated in the study. Adolescents (ages 12–17 years) reported significantly higher pain interference and depressive symptoms, and worse lower extremity physical functioning domain scores compared to younger children (ages 8–11 years). Female participants reported significantly higher pain interference, fatigue, and depressive symptoms, and worse lower extremity physical functioning domain scores compared with their male counterparts. Participants with hip or joint problems that limited usual activities reported significantly higher pain, fatigue, and depressive symptoms scores, and worse upper/lower extremity physical functioning scores as did participants who had experienced sickle pain in the previous 7 days. Conclusions: PROMIS pediatric measures are feasible in a research setting and identify expected differences in known group comparisons in a sample of SCD children. The large domain score differences between those with or without SCD‐related complications suggest the potential usefulness of these measures in clinical research, but further validation studies are needed, particularly in clinical practice settings.